OPTIMIZATION OF POTENCY OF RETRIBUTION PERMIT TO ESTABLISH BUILDING IN INCREASING REAL REGIONAL INCOME IN ALOR REGENCY - Zainudin Adang Djaha (JAKA - Jurnal Jurusan Akuntasi, 2017)
As the fundamental reason for this research is that many people who do not have building permiyt (IMB) in Alor District is Rp12,553,100,000. Realization of Building permit License by local Government of Alor Regency trough Local revenue and asset service and 2010 amounted to 37,23%. This data shows that local government effort in realizing IMB retribition is still very low or not yet optimal. The research questions is How Potential Levy of Building Establishment (IMB) to local Own Revenue (PAD) in Alor Regency. How to optimalized potential levy of Building Establishment Permit (IMB) (PAD)in ALor Regeency. The purpose of this research is to know potential levy of Building Establishment Permit (IMB) to know optimalization of Potential Levy of Building Establishment Permit (IMB). The result showed that local government efforts in realizing IMB terribution is still very low or not optimal. In addition the potential of IMB levy that has not been optimized, among others,in 2010 amounted to Rp 12,531,000,000, in 2011 amounting to Rp 12,529,850,000 and in 2012 the potential of IMB levy not yet optimized is Rp 12,529,360,000. The realization of IMB levy for 2010 amounted to 9,89%,realization of IMB levy for 2011 amounted to 21,69% and the realization of IMB levy for the year 2012 amaounted to 22,49%. From this achievement, it can be concluded that the local government of Alor Regency has not maximized and the realization of IMB levy. IMB levy that has not been optimized for 2010 amounted to 90,11%, the realization of IMB levy that has not been optimized for the year 2011amounted to 79,16% and the realization of IMB levy that has not been optimized for the year 2012 amounted to 79,62%. From this achievement, it can be concluded that the district government of Alor has not yet optimized the IMB levy. The building owner does not have building permit because the requirements set bay the Office of Spatial Planning and Building Alor regency Contained in Local Regulation No.12 of 1998 on the license of Building Establishment is not yet complete. The majority of building owners still do not know about the procedures for the costruction of building permit due to lack of socialization provided by the government